Tanggung Jawab Hukum Jasa Ekspedisi atas Kerugian Konsumen (Studi Kasus di PT Antar Jasa Indonesia) - Dara Puspita; Fani Budi Kartika (Lembaga Yasin AlSys, 2025)
This study is motivated by the ongoing weakness in the implementation of legal responsibility by expedition service providers for consumer losses in the form of lost or damaged goods, despite the existence of consumer protection regulations. The research focuses on the prevailing legal framework, the form of legal responsibility held by PT. Antar Jasa Indonesia as a business operator, and the effectiveness of dispute resolution mechanisms available to consumers. The objective is to provide a comprehensive analysis of the legal basis governing the liability of expedition service providers, the practical implementation of such liability, and the obstacles that hinder effective consumer protection. The methodology employed combines normative and empirical juridical approaches, utilizing statutory, conceptual, and sociological perspectives. Normative analysis was conducted on Law Number 8 of 1999 on Consumer Protection and the Indonesian Civil Code, while empirical analysis involved a case study of claim handling and dispute resolution practices at PT. Antar Jasa Indonesia. The findings reveal that, normatively, business operators are obliged to compensate consumers for losses; however, in practice, the implementation of this responsibility remains suboptimal. Contributing factors include a lack of legal awareness among consumers, weak regulatory oversight, and claim procedures that are insufficiently transparent and inefficient. The study concludes that the legal responsibility of PT. Antar Jasa Indonesia has not yet fully ensured maximum protection for consumers. The implications highlight the need to strengthen consumer complaint systems, enhance corporate transparency and accountability, and harmonize operational standards with consumer protection principles to ensure legal certainty and fairness for all parties.